2017
DOI: 10.1108/ijphm-07-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Choice of mandatory prescribed drugs in Portugal: a consumers’ perspective

Abstract: Purpose This paper aims to contribute to the understanding of what influences consumers’ choice of mandatory prescribed drugs, by looking with more detail to the substitution of branded drugs by generics. Specifically, this research looks at three factors that can influence this decision, namely, participative decision-making, perceived risk and price consciousness, within the recent changes introduced in the Portuguese pharmaceutical market by new legislation. Design/methodology/approach A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(118 reference statements)
1
4
0
Order By: Relevance
“…The idea that patients remain ill-informed about generics, that they only adhere to them because of their low cost and that they distrust those who are very cheap, seems generalized. This price consciousness influence in the intention to buy generic medicines was noted in a previous study (Ferreira and Barbosa, 2017). Findings also revealed that both GPs and PPs respondents were highly concerned about the manufacturing sources of generic drugs and the companies’ trustworthiness.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The idea that patients remain ill-informed about generics, that they only adhere to them because of their low cost and that they distrust those who are very cheap, seems generalized. This price consciousness influence in the intention to buy generic medicines was noted in a previous study (Ferreira and Barbosa, 2017). Findings also revealed that both GPs and PPs respondents were highly concerned about the manufacturing sources of generic drugs and the companies’ trustworthiness.…”
Section: Discussionsupporting
confidence: 71%
“…There is a growing international literature on the attitudes of physicians, pharmacists and/or patients toward generic medicines (Hassali et al , 2009; Colgan et al , 2015; Dunne and Dunne, 2015; Toverud et al , 2015; Dunne, 2016, for reviews), and also many country-specific studies: Portugal (Figueiras et al , 2008; Quintal and Mendes, 2012; Ferreira and Barbosa, 2017); Australia (Chong et al , 2011); Italy (Fabiano et al , 2012); Belgium (Bever et al , 2015); Irland (Dunne et al , 2014a, 2014b); Malasia (Chua et al , 2010); Bosnia and Herzegovina (Čatic et al , 2017); Jordan (El-Dahiyat et al , 2014); Greece (Karampli et al , 2016); Palestine (Shraim et al , 2017); India (Zaverbhai et al , 2017); Turkish (Toklu et al , 2012); Finland (Heikkilä et al , 2011); Saudi Arabia (Salhia et al , 2015); Nigeria (Auta et al , 2014; Fadare et al , 2016); Norway (Kjoenniksen et al , 2006); Japan (Kobayashi et al , 2011), France (Riner et al , 2017). The results seem to indicate that, although generic medicine use has become more widespread, many health professionals and patients hold negative perceptions of generic medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the purposes of this study, the nature of the research and the available resources, data was collected from a convenience sample. Like other studies (Ferreira and Barbosa, 2017; Chan and Tsang, 2018), an online questionnaire was created and sent to respondents who received all the information to complete the questionnaire and share it. The use of a snowball method, which has been commonly used to explore the relationship between brands and consumers, has been seen by researchers (Albert et al ,2008; Valta, 2013), as a valid way to collect data.…”
Section: Methodsmentioning
confidence: 99%
“…This study examines the determinants of purchase intention toward generic drugs among Malaysian. These results are vital because prior studies were conducted in developed countries (mostly in western countries) (Awaisu et al 2014;Colgan et al 2015;Ferreira & Barbosa 2017;Francisquinho 2013;Khadke & Khanda 2017;Masood et al 2016;Shraim et al 2017;Srivastava & Kumar 2014;Wajid et al 2015) consumers' and health care providers' perception and Even though numerous studies on knowledge and perception of safety and efficacy of generic drugs have been conducted in Malaysia, most of the studies were descriptive in nature (Hassali et al 2014b;Kumar et al 2015;Ting et al 2016;Wong et al 2014b)attitudes, and perceptions of generic medicines in low-and middleincome countries (LMICs. There are very limited empirical studies in this area conducted from marketing perspective using structural equation modelling.…”
Section: Theoretical Implicationmentioning
confidence: 99%